2011
DOI: 10.1038/ncomms1252
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints indicate risk of drying in the Amazon basin

Abstract: Climate warming due to human activities will be accompanied by hydrological cycle changes. Economies, societies and ecosystems in south America are vulnerable to such water resource changes. Hence, water resource impact assessments for south America, and corresponding adaptation and mitigation policies, have attracted increased attention. However, substantial uncertainties remain in the current water resource assessments that are based on multiple coupled Atmosphere ocean General Circulation models. This uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…Beyond this model consensus, however, substantial uncertainties in the current assessments given uncertainty in climate feedbacks and climate sensitivity to anthropogenic forcing remain. They arise from many sources including the limited ability of coupled ocean-atmosphere general circulation models (OAGCMs) to capture the presentclimate global patterns of temperature and precipitation as well as local vegetation-climate feedbacks Shiogama et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this model consensus, however, substantial uncertainties in the current assessments given uncertainty in climate feedbacks and climate sensitivity to anthropogenic forcing remain. They arise from many sources including the limited ability of coupled ocean-atmosphere general circulation models (OAGCMs) to capture the presentclimate global patterns of temperature and precipitation as well as local vegetation-climate feedbacks Shiogama et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As noted in the introduction, metrics that are related to future projections have been sought (Hall and Qu 2006;Boe et al 2009;Shiogama et al 2011). Though it is beyond the scope of the present study, it will be valuable to assess briefly whether the simple metrics defined in this study may have any relevance to future projection.…”
Section: Discussionmentioning
confidence: 97%
“…It has been pointed out that most of such straightforward metrics as area-mean biases and root-mean-square errors for the present day climate do not necessarily be applicable well to future projections (Whetton et al 2007;Abe et al 2009;Girogi and Coppola 2010;Knutti et al 2010). Recently, e€orts have been devoted to finding metrics that can connect current climate reproducibility reasonably to future projection (Hall and Qu 2006;Boe et al 2009;Shiogama et al 2011), where these metrics are expected to reduce uncertainty in future projections based on ensembles of climate models. In addition, a new paradigm of a statistically indistinguishable ensemble has been proposed (Annan and Hargreaves 2010), which di€ers from the particular paradigm we adopt here that ensemble members are assumed to be distributed around the true climate.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the credibility of future projections is becoming an increasingly important issue. Some studies constrain projections using observations, suggesting that the models performing well in a present-day climate predict more converged future changes (Walsh et al 2008;Smith and Chandler 2010;Shiogama et al 2011). Abe et al (2009) show that the similarities observed in the precipitation distribution among the models in the present-day climate is significantly correlated with the similarities observed in the projected precipitation change over the tropics (15 S-15 N).…”
Section: Introductionmentioning
confidence: 97%